A cross‐sectional study of mental health in UK veterinary undergraduates. (21st September 2013) - Cardwell, J. M.; Lewis, E. G.; Smith, K. C.; Holt, E. R.; Baillie, S.; Allister, R.; Adams, V. J.
Abstract : Wellbeing (positive mental health) and mental ill‐health of veterinary students from a single UK school were quantified using validated psychological scales. Attitudes towards mental ill‐health and suicide were also assessed. Results were compared with published data from the UK general population and veterinary profession. Of the total student population (N=1068), 509 (48 per cent) completed a questionnaire. Just over half (54 per cent) of the respondents had ever experienced mental ill‐health, with the majority reporting a first occurrence before veterinary school. Student wellbeing was significantly poorer (p<0.0001) than general population estimates, but not significantly different (p=0.2) from veterinary profession estimates. Degree of mental distress in students was significantly higher than in the general population (p<0.0001). Despite the majority (94 per cent) agreeing that 'Anyone can suffer from mental health problems', students were significantly more likely than members of the general population to agree that 'If I were suffering from mental health problems, I wouldn't want people knowing about it' (p<0.0001). Students were more likely to have thought about suicide, but less likely to have made an attempt (p<0.001; p=0.005), than members of the general population. The possibility of non‐response bias must be considered when interpreting findings. However, strong similarities between results from this study population and the UK veterinary profession, as well as other veterinary student populations internationally, suggest no substantial school‐level bias.